Theoretical and Methodological Model of Downshifting as an Alternative Resource of Self-Realization of a Successful Person in Dimensions of Social Transformations - Kozmenko Olena; Mykhailiuk Vitaliy; Chernetska-Biletska Nataliia (Insight: the psychological dimensions of society, 2023)
The purpose of the research is to build a theoretical and methodological model, analyse, systematize and generalize the phenomenon of downshifting as an alternative resource of a person’s self-realization in the conditions of modern society. Methods. The methodology of the research consists of the interpretation of downshifting as a re-achievement of success in changed situations, taking into account a greater number of important conditions and factors. Results. It is stated that the attitude towards downshifters is ambiguous and causes many discussions, but it is important to understand that a person who dared to change their lifestyle may feel happy and self-fulfilled. It means success for this person. It was found that the difficult periods experienced by the modern generation, permanent reforms, the COVID-19 pandemic, then the war on the territory of Ukraine, and the unstable economic and political situation are the testing for social and moral values and a unique opportunity to rethink existence for the sake of positive changes in the future. A theoretical and methodological model of downshifting, which consists of such components as definitions; drives; approaches; forms; the types of people who choose to downshift and the unifying component of the model is operationalization has been built. All components have structural elements that reveal their main content parameters. Modern studies of the outlined problem are analyzed. Attention is focused on such a form of downshifting as an authentic Ukrainian variant. Representatives of the new movement – freegans – have been identified among the types of downshifters. It has been stated and proven that downshifting is a resource for the self-realization of a successful person, one of the options for getting out of a difficult life situation. Discussion and conclusions. It is summarized that the results of the research have significant scientific facts in the dimensions of a person’s self-realization, revealing their potential, and the success of a person in the dimensions of social transformations.